The Role of Organizational Culture and Work Discipline on the Performance of the Presbyter of the GMIT Syalom Oehani Congregation - Adipapa Yanto Haning; Mariam Magdalena Waang; Yudi Setiawan Widjaja; Jacinta Winarto (Jurnal Informatika Ekonomi Bisnis, 2026)
This study aims to analyze the influence of organizational culture and work discipline on the performance of presbyters in GMIT Syalom Oehani Congregation. The research is grounded in the importance of organizational culture as a guiding framework for values, norms, and service behavior, as well as discipline as a determinant of consistency, responsibility, and work effectiveness. The study employs a causal associative design with a quantitative approach. The population consists of 35 presbyters of the Syalom Oehani Congregation, using a saturated sampling technique. Data were collected through Likert-scale questionnaires and analyzed using multiple regression tests with the assistance of SPSS. The results indicate that organizational culture has a positive and significant effect on presbyter performance, and work discipline also has a positive and significant effect on presbyter performance. The study concludes that the integration of a strong organizational culture and high work discipline serves as a key foundation for enhancing the effectiveness of presbyterial service in the GMIT Syalom Oehani Congregation.